The role of spiritual support in combating suicidal ideations: insights from young adults - Mohd munir, Nur Syuhada; Rais, Haniza; Zubairi, Ainol Madziah (AID Academy, 2024)
This research intends to discover the journey of four suicide survivors who have engaged with frequent suicidal ideations and later employed spiritual resources to safeguard themselves against it. Previous studies have discussed at length on spiritual elements to be included as protective factors, but little is known from the Malaysian context and local population. There were four participants recruited for this research. They comprised of four young adults, one female and three males. The participants were selected via purposive sampling based on specified criteria to recruit the participants. Data was gathered through a series of in-depth individual interview sessions that allowed the researchers to explore more of the lived experience of the suicide survivors. Thematic analysis was used for the data analysis of this research. It extracted some salient themes, namely the use of religious bases among the participants in pursuing their suicidal intentions into actions. The generated themes suggest religion as part of one’s immediate thinking process, sense of control, and hopeful feeling. From this research, religion was found to be essential as protective factors, hence offering a possible framework for suicidal intervention that can shed light on the counseling practitioners in addressing the suicide crisis cases. Feeling hopeful was significant, as participants saw it as a sense of motivation to overcome the issues. The findings underscore the spiritual and religious sources as part of a significant aspect that should be embedded into suicide intervention. The findings also advocate for holistic and comprehensive support for individuals who are struggling with suicidal behaviours.